2013
DOI: 10.1007/s13277-013-1199-8
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid family gene expression profiling in breast normal tissue and tumor samples

Abstract: Rhomboid is an evolutionary conserved and functionally diversified group of proteins composed of proteolytically active and inactive members that are involved in the modulation of multiple biological processes such as epidermal growth factor receptor signaling pathway, endoplasmic reticulum-associated degradation, cell death, and proliferation. Recently, several human rhomboid genes have been associated with the development of chronic myeloid leukemia and pituitary, colorectal, ovarian, and breast cancers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…RHBDD2 overexpression was initially described by Abba et al in patients with advanced breast cancer as a consequence of gene amplification events (3). Recently, we described a significant association between RHBDD2 overexpression among breast carcinomas with low/negative progesterone receptor expression (6). In the present study, we demonstrated that RHBDD2 mRNA variants and their coding proteins can be differentially detected in breast tumor and normal specimens.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…RHBDD2 overexpression was initially described by Abba et al in patients with advanced breast cancer as a consequence of gene amplification events (3). Recently, we described a significant association between RHBDD2 overexpression among breast carcinomas with low/negative progesterone receptor expression (6). In the present study, we demonstrated that RHBDD2 mRNA variants and their coding proteins can be differentially detected in breast tumor and normal specimens.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we demonstrated that RHBDD2 mRNA variants and their coding proteins can be differentially detected in breast tumor and normal specimens. As previously described (3,4,6), total RHBDD2 (mRNA and protein) was found to be upregulated in breast carcinomas. However, individual splicing variant analysis allowed us to detect a significant increment in RHBDD2-2 variant expression in breast carcinomas in respect to normal tissues.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A prior report showed that RHBDF1 expression is highly elevated in breast cancer and strongly correlated with increased disease progression, metastasis, poor prognosis, and poor response to chemotherapy [26]. RHBDD2 mRNA and protein are overexpressed in breast cancer [27]. Based on these results, we propose that RHBDD1, a member of Rhomboids, may play a role in colorectal cancer by interacting with EGFR.…”
Section: Introductionmentioning
confidence: 56%
“…RHBDD2 expression has been related to proliferation, migration, and cellular response to ER stress 8 . Over-expression RHBDD2 has also a significant association among breast carcinomas with low-negative progesterone receptor expression 9 . RHBDD2 also involved in ER stress but its specific role is not cleared 10 .…”
Section: Introductionmentioning
confidence: 98%